Two-dye two-color laser-induced fluorescence spectroscopy on droplets of green solvent water/ethanol mixtures for thermometry and mixture composition - Ulrich, Hannah; Weiß, Richard; Zigan, Lars (Experiments in Fluids, 2024)
This work shows new insights on the application of two-color laser-induced-fluorescence (2c-LIF) thermometry in a droplet chain. A two-dye mixture is used in ethanol, water and ethanol/water mixtures in order to reach a high-temperature sensitivity and avoid the detection of lasing effects in the droplets. Various droplet sizes are recorded in regard to the limitation of the detection system for very small micrometric droplets. The breakup of a droplet chain is measured to assess the spectral detection system in applications with liquid structures of different sizes. Additionally, a proposal to expand the 2c-LIF application for studying ethanol/water droplets regarding mixture composition with a third color channel is presented. Forming two intensity ratios, the spectra can be used to obtain information on the mixture composition of the solvent. Measurements in different ethanol/water mixtures containing 0–100 vol% water are evaluated to show this possibility.
CRIS-Team Scopus Importer:2024-08-30